2017
DOI: 10.1007/s11010-017-2969-1
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma

Abstract: Neuronal cell death following spinal cord injury (SCI) is an important contributor to neurological deficits. The purpose of our work was to delineate the function of mammalian sterile 20-like kinase 1 (Mst1), a pro-apoptotic kinase and key mediator of apoptotic signaling, in the pathogenesis of an experimental mouse model of SCI. Male mice received a mid-thoracic spinal contusion injury, and it was found that phosphorylation of Mst1 at the injured site was enhanced significantly following SCI. Furthermore, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Most of them enhanced inflammation and functional recovery [34] . Neuronal cell death following SCI was an important contributor to neurologic deficits [35] . It might be an effective way to improve recovery by promoting neuronal survival via attenuating inflammation after SCI [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of them enhanced inflammation and functional recovery [34] . Neuronal cell death following SCI was an important contributor to neurologic deficits [35] . It might be an effective way to improve recovery by promoting neuronal survival via attenuating inflammation after SCI [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that MST1 activation contributes to neuronal apoptosis and inflammation. Genetic deletion of MST1 may reduce the inflammation and microglial activation after spinal cord injury and ischemic stroke [ 13 , 14 ]. Consistent with these reports, we determined that pharmacological inhibition of MST1 or its knockdown alleviated the neurological deficits, brain edema, and BBB disruption induced by SAH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MST1 exhibits fundamental functions in various central nervous system diseases, including vascular dementia, Alzheimer's disease, amyotrophic lateral sclerosis, and cerebral cavernous malformation [ 9 12 ]. Furthermore, genetic deletion of MST1 provides neuroprotection against ischemic stroke and spinal cord injury by attenuating neuronal apoptosis and the inflammatory response [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence suggests that, among these, neuronal loss [10] and excessive in ammatory response [7] are especially grievous, by causing persistent damage and progressive degeneration of the spinal cord. Attenuation of secondary neuronal death [11], neuroin ammation [12], and demyelination [8] may contribute to the recovery of locomotor function.…”
Section: Introductionmentioning
confidence: 99%